Implementasi Kebijakan Pengembangan SDM di Perguruan Tinggi Kalimantan Timur dalam Mendukung Visi Pendidikan Abad 21 - Chairuddin, Sugeng; Afendi, Achmad Ruslan; Ramli, Akhmad; Kasran, Sudadi; Ridani, Ahmad (Nusantara Innovation Journal, 2024)
Human resource development (HRD) in higher education is a key element in creating educational institutions capable of adapting to global changes in the 21st-century education era. The vision of 21st-century education demands new skills, such as technological literacy, critical thinking, creativity, and collaboration, which must be integrated into the education system, including in higher education institutions. This study aims to analyze the implementation of HRD policies in higher education institutions in East Kalimantan and evaluate how these policies support the 21st-century education vision. This research employs a qualitative approach with a case study method involving several higher education institutions in East Kalimantan. Data were collected through in-depth interviews, observations, and document analysis, involving key stakeholders such as university leaders, faculty, and administrative staff. The data analysis was conducted descriptively using thematic analysis to understand the patterns and processes of HRD policy implementation. The findings indicate that the implementation of HRD policies in higher education institutions in East Kalimantan still faces various challenges, particularly regarding limited technological infrastructure and training resources. However, some universities have taken strategic steps to strengthen faculty and staff competencies through professional development programs aligned with the needs of 21st-century education. These policies have also begun to integrate digital literacy and 21st-century skills into teacher training and development. This study concludes that although the HRD policies in East Kalimantan’s higher education institutions have supported the 21st-century education vision, their implementation still requires improvement, especially in terms of relevant technology and curricula. The study also provides recommendations for policymakers to enhance the synergy between HRD and global demands in education through more comprehensive and sustainable policies.